Osteophytes in the Joints of Patients with Ankylosing Spondylitis: Manifestation of Osteoarthritis or Underlying Disease? - K. D. Dorogoykina; D. S. Sedov; K. N. Safarova; A. P. Rebrov (SINAPS LLC, 2020)
Aim - to study the frequency of peripheral joint damage and the incidence of osteophytes in patients with ankylosing spondylitis.Materials and methods. 124 patients with ankylosing spondylitis corresponding to the international New York criteria of 1984 were examined; 84 men (67,7%). There are two groups of patients: patients aged under 40 years (n=61, men - 44 (72,1%) and over 40 years (n=63, men - 40 (63,5%). In the first group, the median age was 34 [29;38] years, in men - 34,5 [30;37,5] years, in women - 31 [27;38] year; in the second group - 50 [45;56] years, in men - 51,5 [46;54] year, in women - 48 [44;59] years. The activity of the disease was determined, and the results of radiography of the affected joints were evaluated.Results. Clinical and instrumental symptoms of arthritis at the time of study or in history had 82 (66,1%) of the 124 patients with ankylosing spondylitis. Among all patients 111 (89,5%) revealed osteophytes in the peripheral joints, of whom 72 (64,9%) patients had signs of arthritis. Patients with ankylosing spondylitis have both osteoresorption and osteoproliferation on the x-ray.Conclusion. Peripheral arthritis occurred in more than half of patients with ankylosing spondylitis and was associated with higher disease activity. Patients younger than 40 years of age are more likely to have asymmetric arthritis. Most patients had signs of osteoproliferation in the peripheral joints, and the defeat of large joints of the lower extremities prevails. In patients older than 40 years osteophytes are more often detected, more groups of joints are involved in the process, the joints of the hands and feet are affected.